Pengaruh Pemberian Patient Information Leaflet (PIL) dan SMS Motivasi Terhadap Pengetahuan, Persepsi, dan Kepatuhan Pasien Hamil di Pelayanan Primer - Susan Fitria Candradewi; Ginanjar Zukhruf Saputri; Adnan Adnan; Dyah Purmi Ta Arum; Herlanisa Yuliana (JURNAL ILMU KEFARMASIAN INDONESIA, 2021)
Based on data from WHO (World Health Organization), it is estimated that 41.8% of anemia occurs in pregnant women, with the highest prevalence rate of 61.3% in Africa and 52.5% in Asia. Pharmacist interventions have shown a positive effect in improving therapeutic adherence to hypertensive patients, as well as diabetes mellitus who routinely taking the drugs. The aim of the study was to know effect of giving patient information leaflet (PIL) along with motivational SMS on knowledge, perception, and compliance of pregnant patients in primary care. This study used a quasi-experimental method with pre-post design for two groups, the control group who received the Patient Information leaflet (PIL) and the intervention group who received the Patient Information leaflet (PIL) and motivational SMS from the researcher. Statistical analysis using SPSS with paired t test was used to determine differences in knowledge, perceptions and patient compliance before and after the intervention. Respondents who met the inclusion and exclusion criteria in this study were 74 patients. In the control group the mean score showed a significant difference was the knowledge of iron supplementation with p value= 0.001. Whereas in the treatment group, the mean score showed a significantly different were knowledge of iron supplementation and patient compliance with p values ​​were 0.002 and 0.001.